Proper Inclusion Between Vanishing Morrey Spaces and Morrey Spaces - Nicky Kurnia Tumalun (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2021)
In this paper, we give an explicit function which belongs to the Morrey spaces but not in the vanishing Morrey spaces. Therefore, we obtain that the Morrey spaces contain the vanishing Morrey spaces properly.